The Cointegration test for macroeconomic variables and the stock market index: evidence from the stock exchange of Thailand - Jun Jiang (2015)
The study tests the association between selected macroeconomic variables and the stock market index for given periods from the Stock Exchange of Thailand. In the empirical analysis, the monthly data from January 2002 to December 2007 are used for performing the unit root test, Augmented Dickey-Fuller (ADF) test, and the cointegration Jonhasen tests. The representative proxies for macroeconomic influences are, the manufacturing production index, consumer price index, monetary supply, and the exchange rate. The finding shows that all macroeconomic variables, except the exchange rate, have a non-significant association with the movement of the Thai stock market index in short term. With higher fluctuations of the exchange rate, the movement of the Thai stock market expresses higher uncertainty.